A vinculação da gestão de bens públicos às funções sociais da cidade - Mukai, Sylvio Toshiro (2015)
This thesis has the purpose of demonstrating that the management of the public assets is linked to the development of the city`s social function, as required by the Brazilian Federal Constitution and applicable law. The link which this thesis aims at demonstrating withdraws parcel of the discretionary power the Public Administration had to manage its assets directly or by means of granting the private use of the public assets on behalf of a private party. The reduction of the discretionary power results from the necessity of the Public Administration, especially the Municipality, of performing actions and activities aiming at achieving the goals of the urban development policies set forth in the Brazilian Federal Constitution and, in doing so, abiding by the general guidelines provided in the City Act (in Portuguese, Estatuto da Cidade ). Therefore, from an analysis of the current scenario of the Brazilian cities and their relationship with the right to sustainable cities, this thesis aims at defining the so-called social functions of the city . It also aims at establishing the relationship of the city`s social functions with the right to sustainable cities and the social rights, in order to define, by means of the exercise of the public functions which require broad popular participation the way the content and the shape of the intended development of the social functions of the city influence the uses of the public assets and limit the discretionary power of the Public Administration to manage the public assets, directly or by means of grants of the use of such assets by private parties. The goal is to contribute with the ones who require clear and effective fulfillment of the objectives and purposes of the public policy legally formed for the urban development of the Brazilian cities. The preparation of this thesis was based on a systematic interpretation of the applicable constitutional and legal provisions, and also an analysis of Scholar`s opinions and judicial precedents related to the core matter under analysis